Komunikasi Pemasaran Terpadu Taman Pendidikan Al-Qur’an “X”: Pendekatan Community Based Research - Wahyudiyanto, Dhanny (Tanzhim: Jurnal Dakwah Terprogram, 2024)
Organizations that want to achieve success in marketing their products or services need to determine the right promotional method. Promotion does not only need to be carried out by business-oriented companies. Non-profit organizations, including Taman Pendidikan Al-Quran (TPQ), also need to determine appropriate promotional methods for the services they offer to attract the interest of their target market. TPQ "X" before the Covid-19 pandemic had a large number of students. However, during the pandemic the number of students decreased drastically. Even though the pandemic status has been lifted, the number of TPQ "X" students has still not increased. TPQ administrators are having difficulty trying to restore the number of students to as many as before the pandemic. This paper uses integrated marketing communications theory to determine the best promotional design for TPQ "X". The method used is qualitative with a community-based research (CBR) approach. Efforts made together with TPQ administrators show that integrated marketing communications through the process of placing advertising billboards, sales promotions, utilizing WhatsApp media groups for direct mobile marketing and personal sales ultimately succeeded in increasing the number of students who subscribe. A few weeks after implementation, the number of new students registering increased to dozens of children. This paper describes the application of integrated marketing communications at micro-scale da'wah institutions.